2022
DOI: 10.1186/s40878-022-00323-y
|View full text |Cite
|
Sign up to set email alerts
|

Hong Kong’s new wave of migration: socio-political factors of individuals’ intention to emigrate

Abstract: With a recent surge in the outward movement of the population, a new wave of emigration has been suggested to have started in Hong Kong. It is speculated that recent socio-political changes in Hong Kong may have contributed to this phenomenon. Therefore, five socio-political variables—mobility, sense of place, trust and confidence in the law and the legal system, global citizenship, and perception of inequality—are employed in this study as proposed determinants to investigate the intention of Hong Kong reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…In the past few years, after the Anti-Extradition Bill movement in 2019 and the subsequent implementation of the National Security Law in July 2020, a new wave of migration, marked by a record-high rate of outward movement of the population, was observed (Chan et al, 2022;Lui et al, 2022). Similar to the last wave, social and political concerns, including the loss of confidence in the legal system, worries about deterioration of human rights, fear of changes in lifestyle and intention to obtain an alternative citizenship, have been suggested to be the major drivers of migration (Chan et al, 2022;Ho, 2023;Lee et al, 2023;Lui et al, 2022;Ngan et al, 2023). Countries including the United Kingdom, Canada, Australia and the United States remained popular migration destinations for Hong Kong people.…”
Section: Migration Waves In Hong Kongmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few years, after the Anti-Extradition Bill movement in 2019 and the subsequent implementation of the National Security Law in July 2020, a new wave of migration, marked by a record-high rate of outward movement of the population, was observed (Chan et al, 2022;Lui et al, 2022). Similar to the last wave, social and political concerns, including the loss of confidence in the legal system, worries about deterioration of human rights, fear of changes in lifestyle and intention to obtain an alternative citizenship, have been suggested to be the major drivers of migration (Chan et al, 2022;Ho, 2023;Lee et al, 2023;Lui et al, 2022;Ngan et al, 2023). Countries including the United Kingdom, Canada, Australia and the United States remained popular migration destinations for Hong Kong people.…”
Section: Migration Waves In Hong Kongmentioning
confidence: 99%
“…At the same time, their emigration‐related intentions and decisions can be influenced by social, cultural, economic and political factors. It has been suggested that socio‐political factors played a crucial role in shaping the emigration intentions of people in Hong Kong during the post‐2019 period (Chan et al, 2022; Lui et al, 2022). Having determined the reasons that are driving people to leave, identifying the demographic groups that are more likely to leave or have left could be another step towards diagnosing the potential impacts of emigration on the origin society and, in this case, exploring and identifying potential emigrants from Hong Kong.…”
Section: Introductionmentioning
confidence: 99%
“…Scholarly discourse around international mobility continues to grow. While some studies focus on explaining why migration occurs (Kassim & Mat Zin, 2011) and delve into the integration dilemma facing both migrant communities and host societies (Dahinden, 2016), there is growing scholarly discourse focusing on the lack of mechanisms to protect migrant workers, which eventually contributes to the exploitation and criminalization of migrant communities (Chan et al, 2022;Rother, 2017). Other studies have focused on the migrants' settlement, displacement, and the lived experiences of migrants in urban settings globally, and the link to super-diversity (Vertovec, 2007;Schiller & Caglar 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is worth pointing out that many of the studies mentioned above operate with the assumption that individuals who have recently left Hong Kong are necessarily active in political matters. Although the implementation of the National Security Law did constitute a significant push factor for most, many Hongkongers have long considered the possibility of migration before 2019, often motivated by multiple and intersecting factors related to economic capital, educational level, family configuration and social inequalities (Chan et al, 2022;Lui et al, 2022;Li & Liao, 2023). In fact, the relaxation of immigration options, such as those offered by Canada and the United Kingdom, has only served as a catalyst expediting many Hongkongers' plans to leave.…”
Section: Introduction: Queer Processes Of Global Hong Kong Post-2019mentioning
confidence: 99%